Kempfield Silver, Barite and Base Metal (Pb-Zn) Deposit, Lachlan Orogen, Eastern Australia - D Timms (The Australasian Institute of Mining and Metallurgy, 2011)
The Kempfield deposit is located in the Hill End Trough, one of several intracratonic basins developed during Silurian–Devonian time, in the eastern province of the Lachlan Orogen, Eastern Australia.The deposit contains an oxide resource of 5.8 Mt @ 58 g/t Ag and a sulfide resource of 14.4 Mt @ 45 g/t Ag, 1.7 per cent Zn and 0.6 per cent Pb, classified and reported in compliance with the JORC Code. The deposit has been previously explored by a number of companies, including INCO, Shell, Jones Mining, Golden Cross Resources and recently Argent Minerals Ltd (Argent). Argent is currently completing a definitive feasibility study with a view to mining the deposit.The deposit is hosted at the boundary between the Molong High to the west, comprising Ordovician sediments and volcanic rocks and the Hill End Trough to the east, interpreted as a back-arc basin containing Silurian sediments and siliceous-feldspathic volcanic rocks. The boundary between these two strato tectonic units is an imbricate thrust fault zone known as the Copperhannia Thrust.The Kempfield deposit is hosted in felsic volcanic rocks known as the Kangaloolah Volcanics. These have been in-faulted and folded into the Middle Ordovician meta-sediments of the Coombing Formation of metasediments along the Copperhannia Thrust. The Kangaloolah Volcanics belong to the Late Silurian Mumbil Group, comprising submarine carbonate-shale facies interspersed with extensive felsic volcanic piles, which grade conformably upwards into turbiditic sandstone and siltstone sequences (interpreted to represent a deeper depositional environment). These turbiditic rocks are known as the Campbells Formation, comprising siltstone, sandstone and andesitic tuff. The rocks at Kempfield are metamorphosed to lower greenschist facies, reflected through the different type of schists.Silver, gold, lead, zinc mineralisation is hosted in barite-rich horizons, near the boundary to quartz-phyric tuffaceous rocks in submarine, immature, reworked felsic ash tuffs. Barite appears to be hosted in greatest concentrations by the coarser grained volcanoclastic sandstones and grits, whilst intercalated siltstones are volumetrically minor and tend to return low barite and silver. Mineralisation is hosted in stratiform and probably stratabound barite-rich horizons. A northeast-trending, steeply dipping, metamorphic cleavage (S1) occurs throughout the project area.